Dentinal hypersensitivity - Nnaji, Chukwuemeka; Nwatu, Jessica C.; OCHIAGHA, Clara S.; OKOLO, Paschaline U.; NWACHUKWU, Joy O.; ONYEABOR, Heaven C. (Orapuh Journal, 2021)
Dentinal hypersensitivity (DHS) is a common and significant dental condition typically characterized by a brief sharp pain in response to exogenous, non-noxious stimuli. This condition negatively affects patients’ quality of life and may disturb their eating, drinking, brushing, and sometimes even breathing. The exact nociceptive mechanisms of DHS have not been elucidated. In this paper, the authors carried out a narrative review and explored the etiopathogenesis, presumed mechanisms, risk factors, and epidemiology of DHS. They provided guidelines and suggestions for its diagnosis and management. The process of writing took place over one month, between August 30, and September 30, 2021. During this period, the authors sought relevant works online using various databases like PubMed, Core, Z-library, and Google scholar. Google and Edge search engines were used to obtain the required literature using keywords like “dentinal hypersensitivity”, “tooth sensitivity”, “cervical sensitivity”, “dentin sensitivity”, “cervical hypersensitivity”, etc. The authors extracted and documented vital information from different original articles and textbooks based on the objectives of this work. Included in this paper were systematic reviews on DHS published in the English Language. Articles that are unrelated to the topic, whose full-text was not available, and articles that were not written in the English Language were excluded. The most important risk factors for DHS seem to be the frequency and methods of tooth brushing. Thus, dental healthcare personnel (especially dental therapists) should intensify their effort in educating patients on oral hygiene and proper tooth brushing techniques. A better understanding of the underlying nociceptive mechanisms of DHS will lead to the development of improved, simple, efficient, permanent, and low-cost management techniques for the treatment of patients experiencing DHS.